Analisis Kesesuaian Kondisi Objek Wisata Taman Hutan Raya Lati Petangis Dengan Prinsip Wisata 4A - Wana Haryani; Ajeng Nugrahaning Dewanti; Elin Diyah Syafitri; Devi Triwidya Sitaresmi (COMPACT: Spatial Development Journal, 2023)
Tourism is a journey from one place to another which is temporary and is carried out by individuals or groups, this is done as an effort to seek pleasure and harmony with the environment both in natural, cultural, scientific and social dimensions (Wijianto, 2013) In improving the economy of a city, tourism is able to become one of the sectors that has the potential to encourage an increase in the economy. developing important components in tourism, namely the components of attractions, accessibility, amenities, and activities (Lilyk Eka 2021). Based on the 2015-2035 Regional Spatial Plan, Paser Regency has various natural potentials that can be developed, one of which is the tourism sector. By developing the natural potential and local attractions of the Lati Petangis Forest Park, this will be able to attract tourists to visit, especially on national holidays. This is also supported by the government which plans for the Lati Petangis Forest Park area to be developed into a mainstay tourist location in Paser Regency (Paser Regency Environmental Service, 2018). Selection of the Lati Petangis Grand Forest Park Area so that it can be developed into a mainstay tourist area in Paser Regency with tourist attractions that can support existing potentials such as lakes and natural scenery, so that they can attract tourists to visit and enjoy attractions, supported by good accessibility, and able to provide benefits for visitors. Based on the conditions of the tourist object area, it is necessary to evaluate the existing conditions of attractions, accessibility, amenities, and activities in the Lati Petangis Grand Forest Park Area so that development can be carried out as one of the strategies in supporting the development of the tourism sector in Paser Regency and being able to attract the attention of tourists to visit and enjoy the beauty of nature in it. The approach used in this study is a descriptive quantitative approach by using a descriptive format to explain the description of the data obtained during data collection which is then calculated on each variable. In this study, the population was used, namely the Lati Petangis Grand Forest Park tourist attraction area and in collecting data in this study did not use a sample. The data collection technique used is primary data obtained from primary surveys on each variable. The data obtained was then analyzed using a descriptive comparative analysis method with calculations that resulted in a percentage of suitability of the existing conditions of the Lati Petangis Grand Forest Park tourist attraction. Overall the results of the analysis carried out obtained the suitability conditions for the Lati Petangis Raya Forest Park tourist attraction in moderate conditions with a total percentage of 53.3%, this indicates that the existing condition of the Lati Petangi Grand Forest Park tourist attraction is in accordance with the guidelines so that it can carried out the development of the Lati Petangis Grand Forest Park tourist attraction. Keywords : Conformity Analysis, 4A, Tourism Principles, Grand Forest Park